Periradicular corticosteroid infiltration for radicular pain - comparison of Diprophos and Depomedrone and ozone effects - Krahulík, David; Vaverka, Miroslav; Hrabálek, Lumír; Pohlodek, Daniel; Jablonský, Jakub; Valošek, Jan; Zapletalová, Jana (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2023)
OBJECTIVES: To determine the treatment effect of corticosteroids in periradicular therapy (PRT) for radicular pain and to compare different types of corticosteroids and ozone. We also examined the effect in different indication groups for periradicular therapy for each type of treatment agent. BACKGROUND: Various studies have examined the therapeutic value of periradicular infiltration using treatment agents consisting of local anesthetic and corticosteroids or ozone application for radicular pain. This is the first study to compare different types of corticosteroids and ozone. METHODS: Eligible patients with radicular pain who failed conservative management were divided into five indication groups and prospectively followed to assess the PRT effect of corticosteroids or ozone application. PRT was performed under computer tomography (CT) monitoring. A set of three PRT applications in three weeks was applied and the outcome was evaluated using a visual analogue score for back and leg pain. The in-group and between-group treatment effect was tested using the Wilcoxon signed-rank test and the Kruskal-Wallis H-test with Dunn's post-hoc tests, respectively. The dependency between treatment effectiveness and indication for each group was tested using the Kruskal-Wallis H-test and Dunn's post-hoc tests. RESULTS: We prospectively followed 150 patients, randomized into three groups of 50 patients each. The follow-up rate was 100%. All three treatment agents showed a statistically significant treatment effect (P<0.001). The statistically significant effect was higher in betamethasone (Diprophos) versus methylprednisolone (Depomedrone) (P=0.019) and Diprophos versus ozone (P<0.001). Diprophos also showed the highest decrease of VAS after therapy versus VAS prior to therapy (median decrease = 4) compared to Depomedrone and ozone (median decrease = 3 and 2, respectively). The statistically significant outcome was better with the indication of spondylolisthesis and disc herniation (P=0.019) indication for the Diprophos group and between spinal stenosis and spondylolisthesis (P=0.022) and spondylolisthesis and disc herniation (P=0.016) for the ozone group. CONCLUSION: Clinical improvement occurred in all three groups but Diprophos showed the statistically best treatment effect compared to Depomedrone and ozone. Disc herniation resulting in radicular pain had a statistically significant better effect in comparison with spondylolisthesis in the Diprophos and ozone groups, but the ozone group showed heterogeneity depending on treatment effect and indication.
Keywords: Pain; výsledek terapie; Intervertebral Disc Displacement; Humans; Ozone; betamethason; lidé; Prospective Studies; Adrenal Cortex Hormones; bederní obratle; výhřez meziobratlové ploténky; Lumbar Vertebrae; Spondylolisthesis; hormony kůry nadledvin; Betamethasone; bolest; Treatment Outcome; prospektivní studie; spondylolistéza; ozon